PERCEPÇÃO MATERNA DA POLINEUROPATIA PERIFÉRICA: UM RELATO DE EXPERIÊNCIA - Freitas Nascimento, Marcelo Victor; Maria Mello Viana, Lívia; Victor Costa Santos, Manoel; de Andrade Chaves, Mariana; dos Santos Costa, Elizama; Lira de Carvalho, Joanny Isabelly; Cordeiro da Silva, Ilka (SANARE - Revista de Políticas Públicas, 2015)
-